KINETICS OF THE ALBITE-SANIDINE TRANSFORMATION IN THE PRESENCE OR ABSENCE OF QUARTZ - Alekseev V.G.; Medvedeva L.S. (My University, 2006)
The experiments were conducted with fractions of low albite, intermediate sanidine, and α-quartz crushed to 50–100 μm. The fractions were repeatedly rinsed with water in an ultrasonic bath to remove dust particles. The specific surface of albite and sanidine measured by the BET method is 0.11 m2/g. We performed four experimental series with different amounts of minerals (in mg) per 1 ml 0.1 m KHCO3.
Keywords: albite; sanidine